Acinetobacter pakistanensis Abbas et al. 2014 is a later heterotypic synonym of Acinetobacter bohemicus Krizova et al. 2014 - Nemec, Alexandr; Radolfova-Krizova, Lenka (International journal of systematic and evolutionary microbiology, 2016)
Two novel species names, Acinetobacter bohemicus and Acinetobacter pakistanensis, appeared on validation list no. 161 (January 2015) under priority numbers 26 and 28, respectively. As the published data suggested a high similarity of the organisms associated with these names, we aimed to define their taxonomic relationship. The study set included all strains used in the original nomenclatural proposals, i.e. 25 strains of A. bohemicus and one strain of A. pakistanensis. The average nucleotide identity values (95.9 and 96.1 % based on blast and MUMmer, respectively) between the whole-genome sequences of A. bohemicus ANC 3994T and A. pakistanensis KCTC 42081T supported the identity of these type strains at the species level. Based on the genus-wide comparative analyses of the rpoB sequences and whole-cell fingerprints generated by matrix-assisted laser desorption/ionization-time-of-flight MS, A. pakistanensis KCTC 42081T fell within the respective clusters formed by the 25 A. bohemicus strains. The same picture was obtained on the basis of comparative analysis of 16S rRNA gene sequences of KCTC 42081T and three A. bohemicus strains. Finally, the metabolic and physiological features of KCTC 42081T were found to be congruent with those of A. bohemicus. Based on these results, we conclude that Acinetobacter pakistanensis is a later heterotypic synonym of Acinetobacter bohemicus.
Keywords: sekvenční analýza DNA; Sequence Analysis, DNA; spektrometrie hmotnostní - ionizace laserem za účasti matrice; RNA, Ribosomal, 16S; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; RNA ribozomální 16S; Acinetobacter; DNA, Bacterial; Phylogeny; fylogeneze; techniky typizace bakterií; Bacterial Typing Techniques; DNA bakterií